2004
DOI: 10.3201/eid1010.040042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Transmission Analysis ofHelicobacter pyloriStrains within a Family1

Abstract: Point mutations, intragenic recombination, and introduction of foreign alleles enhanced strain diversity within the family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 34 publications
6
63
0
1
Order By: Relevance
“…Although multiple strains have not been sequenced for all individuals in this study, we have shown that within-individual sequence diversity is low. This low within-individual genetic diversity, combined with the observation of dominant strains (Raymond et al 2004), provides support for the single-strain assumption used in this study. Indeed, several recent studies that have sequenced multiple strains found substantially lower sequence divergences within individuals (Israel et al 2001, Raymond et al 2004, Kraft et al 2006, suggesting a shared common ancestor for multiple strains within individuals.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Although multiple strains have not been sequenced for all individuals in this study, we have shown that within-individual sequence diversity is low. This low within-individual genetic diversity, combined with the observation of dominant strains (Raymond et al 2004), provides support for the single-strain assumption used in this study. Indeed, several recent studies that have sequenced multiple strains found substantially lower sequence divergences within individuals (Israel et al 2001, Raymond et al 2004, Kraft et al 2006, suggesting a shared common ancestor for multiple strains within individuals.…”
Section: Discussionsupporting
confidence: 48%
“…Multiple strain data generated in this study (mutY: 3 individuals, 66 pairwise comparisons; ureI: 2 individuals, 28 pairwise comparisons) indicated low average within-individual genetic distances (mutY: 0.006 6 0.01, n ¼ 19; ureI: 0.014 6 0.013, n ¼ 12). Furthermore, Raymond et al (2004) sequenced 20 cultures for each of 6 individuals and detected a maximum of four strains per individual, where each individual appeared to be infected by a dominant strain with .70% occurrence. Mean average ureC genetic distance within individuals was low (0.023 6 0.004, n ¼ 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission within families occurs for many indigenous organisms (14) and can resemble inheritance patterns (55). Furthermore, whether a microbe is acquired from a family member (and so is preadapted to the next host) or from a genetically unrelated stranger could modify the risk of a disease that may present clinically decades later (46).…”
Section: Biological Considerationsmentioning
confidence: 99%